Corporal punishment of children in theoretical perspective - Donnelly, Michael, 1949-; Straus, Murray A. (Murray Arnold), 1926- (Yale University Press, 2005)
Despite being commonplace in households a generation ago, corporal punishment of children has been subjected to criticism and shifting attitudes in recent years. Many American school districts have banned it, and many child advocates recommend that parents no longer smack or strike their children. In this book, social theorist Michael Donnelly and family violence expert Murray Straus tap the expertise of social science scholars and researchers who address issues of corporal punishment, a subject that is now characterised as a key issue in child welfare. The contributors discuss corporal punishment, its use, causes and consequences, drawing on a wide array of comparative, psychological and sociological theories. Together, they clarify the analytical issues and lay a strong foundation for future research and interdisciplinary collaboration.